Symmetric Sodium-Ion Capacitor Based on Na0.44MnO2 Nanorods for Low-Cost and High-Performance Energy Storage - Chen, Zhongxue; Yuan, Tianci; Pu, Xiangjun; Yang, Hanxi; Ai, Xinping; Xia, Yongyao; Cao, Yuliang (ACS applied materials & interfaces, 2018)
Batteries and electrochemical capacitors play very important roles in the portable electronic devices and electric vehicles and have shown promising potential for large-scale energy storage applications. However, batteries or capacitors alone cannot meet the energy and power density requirements because rechargeable batteries have a poor power property, whereas supercapacitors offer limited capacity. Here, a novel symmetric sodium-ion capacitor (NIC) is developed based on low-cost Na0.44MnO2 nanorods. The Na0.44MnO2 with unique nanoarchitectures and iso-oriented feature offers shortened diffusion path lengths for both electronic and Na+ transport and reduces the stress associated with Na+ insertion and extraction. Benefiting from these merits, the symmetric device achieves a high power density of 2432.7 W kg–1, an improved energy density of 27.9 Wh kg–1, and a capacitance retention of 85.2% over 5000 cycles. Particularly, the symmetric NIC based on Na0.44MnO2 permits repeatedly reverse-polarity characteristics, thus simplifying energy management system and greatly enhancing the safety under abuse condition. This cost-effective, high-safety, and high-performance symmetric NIC can balance the energy and power density between batteries and capacitors and serve as an electric power source for future low-maintenance large-scale energy storage systems.